The Indo-West Pacific Pilumnidae XVIII: On the taxonomy of Pilumnus scabriusculus Adams and White, 1849, and P. sluiteri De Man, 1892, with a note on Cancer incanus Forskål, 1775 (Brachyura: Xanthoidea) - Ng, Peter K.l.; Clark, Paul F. (Zootaxa, 2005)
The taxonomy of two Indo-West Pacific species of pilumnid crabs, Pilumnus scabriusculus Adams & White, 1849, and P. sluiteri De Man, 1892, is clarified. Pilumnus sluiteri has long being synonymised under P. scabriusculus but re-examination of the types and other material shows that there are distinct differences between them, notably in the form of the carapace, mouthparts, chelipeds and male first pleopods. They are here regarded as two distinct species.